ALIGNMENT EFFECTS IN THE MULTIPLE PHOTON IONIZATION OF NITRIC-OXIDE - Booth, J; Bragg, S; Hancock, G (1985)
1+1 resonantly enhanced multiple photon ionisation of NO(X 2Πi) via the A 2Σ+ state at wavelengths near 226 nm gives ion signals which depend upon the value of {norm of matrix}ΔJnorm of matrixin the A-X transition, with P, R branch excitation being enhanced over Q branch excitation. The results are interpreted in terms of ionisation of aligned NO A 2Σ+ molecules, and imply that the electron departs primarily as a pσ wave. Implications for the measurements of ground state NO populations via two-step ionisation are discussed. © 1985.